Long-term left ventricular ejection function in fulminant and non-fulminant myocarditis: A multicenter study in China - Guangling Li; Jing Zhang; Zheng Xu; Yaogui Ning; Li Zhang; Jing Yang; Gang Chen; Fan Li; Jiangang Jiang (International Journal of Cardiology: Heart & Vasculature)
Background: There is a gap regarding comparisons of left ventricular ejection fraction (LVEF) changes between fulminant myocarditis (FM) and non-FM (NFM) patients at different follow-up intervals. Methods: This multicenter retrospective study included 324 patients (163 FM and 161 NFM) with confirmed acute myocarditis through endomyocardial biopsy (EMB) or cardiac magnetic resonance imaging. We used multi-model adjustment approach and a mixed-effects model to comprehensively evaluate changes in LVEF in FM relative to NFM, considering both dichotomous outcome (primary outcome) and repeated measurements outcome (secondary outcome). Sensitivity analysis was conducted for patients aged 15 years and older. Results: FM patients exhibited a higher risk of the primary outcome (LVEF < 55 % at the last two follow-up visits) compared to NFM patients, with an odds ratio (OR) of 8.517 (95 % CI, 4.666–16.552; P < 0.001). Following comprehensive adjustment for confounders, the OR for FM versus NFM was 7.438 (95 % CI, 3.967–14.763; P < 0.001). Analysis of repeated measurements (secondary outcome) revealed that LVEF in the NFM group surpassed that in the FM group at different follow-up time points. Consistent findings were observed in the sensitivity analysis population. Additionally, after adjusting for potential confounders, intra-aortic ballon pump (IABP) and extracorporeal membrane oxygenation (ECMO) demonstrated OR values of 0.030 (95 % CI: 0.002–0.197; P = 0.001) and 0.339 (95 % CI: 0.124–0.880; P = 0.030) in patients with FM, respectively. Conclusion: FM patients face a lower LVEF compared to NFM patients across various follow-up intervals. Additionally, early application of IABP and ECMO can enhance long-term LVEF in patients with FM.